Striking between-population floral divergences in a habitat specialized plant. - Sumayya Abdul Rahim (Public Library of Science (PLoS), 2021)
When the habitat occupied by a specialist species is patchily distributed, limited gene flow between the fragmented populations may allow population differentiation and eventual speciation. 'Sky islands'-montane habitats that form terrestrial islands-have been shown to promote diversification in many taxa through this mechanism. We investigate floral variation in Impatiens lawii, a plant specialized on laterite rich rocky plateaus that form sky islands in the northern Western Ghats mountains of India. We focus on three plateaus separated from each other by ca. 7 to 17 km, and show that floral traits have diverged strongly between these populations. In contrast, floral traits have not diverged in the congeneric I. oppositifolia, which co-occurs with I. lawii in the plateaus, but is a habitat generalist that is also found in the intervening valleys. We conducted common garden experiments to test whether the differences in I. lawii are due to genetic differentiation or phenotypic plasticity. There were strong differences in floral morphology between experimental plants sourced from the three populations, and the relative divergences between population pairs mirrored that seen in the wild, indicating that the populations are genetically differentiated. Common garden experiments confirmed that there was no differentiation in I. oppositifolia. Field floral visitation surveys indicated that the observed differences in floral traits have consequences for I. lawii populations, by reducing the number of visitors and changing the relative abundance of different floral visitor groups. Our results highlight the role of habitat specialization in diversification, and corroborates the importance of sky islands as centres of diversification.